Capital budgeting and procurement practices - Burger, Philippe (OECD Publishing, 2013)
Capital investment is a key function of government. However, for a number of reasons it has proven difficult for governments to ensure that capital investment represents value for money, is affordable, and is budgeted and accounted for in a prudent and transparent manner. This article discusses these challenges facing governments. Using the findings of a survey conducted among OECD countries and enhanced engagement countries in 2012, this article provides an overview of what governments are doing with respect to planning and prioritisation, procurement, construction, operation and management, monitoring and evaluation, and budgeting and accounting for capital projects. The article concludes with a number of recommendations for capital budgeting and procurement. JEL classification: H400, H540, H570 Keywords: Capital investment, capital budgeting, capital projects, value for money, budgeting systems, accounting systems, transparency, procurement, public-private partnerships, PPPs, TIP, traditional infrastructure procurement